Service industries and regions : growth, location and regional effects - Cuadrado-Roura, Juan R. (Advances in Spatial Science, The Regional Science Series, 2013)
The service sector in most advanced economies accounts for up to seventy percent of employment and GDP and, given its growing importance, has received much research attention over the last two decades. However, not very much attention has been paid to the relationship between this sector and both its terrritorial impact and regional effects. The main objective of this book is to offer a comprehensive approach to these aspects, focusing particularly on the location factors of service industries and the importance of some specific services, such as business services and knowledge and information services. The contributions have been prepared by well-known experts in the field from a wide number of countries. The focus of all contributions is not only on theoretical aspects, but also provides empirical analyses on specific countries and topics such as the geographical concentration, globalization impacts, foreign direct investments, and innovation.